Considerations of force plate transitions on centre of pressure calculation for maximal velocity sprint running - Exell, T. A.; Gittoes, M. J. R.; Irwin, G.; Kerwin, D. G. (Sports Biomechanics, 2012)
The aims of this study were to evaluate the accuracy of centre of pressure (COP) data obtained during transition of load across the boundary between two force plates, and secondly to examine the effect of such COP data on joint kinetics during sprint running performances. COP data were collected from two piezoelectric force plates as a trolley wheelwas rolled across the boundary between the plates. Position data for the trolley were collected using an opto-electronic motion analysis system for comparison with COP data. Mean COP errors during transition across the plate boundary were 0.003 ^ 0.002m relative to a control point.Kinematic andkinetic datawere also collectedfromeight athletesduring sprint runningtrials to demonstrate the sensitivity of the inverse dynamics analysis toCOPerror for the ground contact phase of the dynamic movement trials. Kinetic sensitivity to the COP error was assessed during the entire stance phase for the ankle, knee, and hip joints and was less than 5% and 3%for joint moment and power data, respectively. Based on the small COP error during transition across plate boundaries, it is recommended that foot contacts overlapping two force plates may be included in inverse dynamics analyses.